Patient and Surgeon Expectations Prior to Anterior Cruciate Ligament Reconstruction. Issue 3 (October 2018) - Khair, Mahmoud Michael; Ghomrawi, Hassan; Wilson, Sean; Marx, Robert G.
Background: When discussing potential treatment with patients choosing to undergo surgery for disruption of the anterior cruciate ligament (ACL) and their families, surgeons spend considerable time discussing expectations of the short- and long-term health of the knee. Most of the research examining patient expectations in orthopedic surgery has focused largely on arthroplasty. Questions/Purposes: The purpose of this study was to quantitatively assess the differences between the patient's and the surgeon's expectations before primary anterior cruciate ligament reconstruction (ACLR). Methods: In this case series, we prospectively enrolled 93 patients scheduled for primary ACLR between 2011 and 2014. Expectations were measured using the Hospital for Special Surgery 23-item Knee Expectations Survey; scores were calculated for each subject. Results: In all but six categories, patients had expectations that either aligned with their surgeons' or were lower. The largest discordance between surgeon and patient expectations in which the patient had lower expectations was employment; 75% of patients had similar expectations to the surgeon when asked if the knee would be "back to the way it was before the problem started, " less than 1% had higher expectations, and 17% had lower expectations. Conclusion: In general, patient expectations align well with surgeon expectations. Patients who are older, have a lower activity level, and who have selected allograft over autograft for ACLR could also be at risk for greater discordance. Understanding these differences, and their predictors, will help guide physicians when they are counseling patients about ACLR and also help them interact with patients after surgery as they assess outcomes.